The hepatoprotective activity of olive oil and Nigella sativa oil against CCl(4) induced hepatotoxicity in male rats - Al-Seeni, Madeha N. (BMC Complement Altern Med, 2016)
BACKGROUND: Liver disease is the major cause of serious health problem leading to morbidity and mortality worldwide and the problem has increased in search for hepatotherapeutic agents from plants. The present study was designed to compare the probable hepatoprotective activity of olive oil and N. sativa oil on CCl(4) induced liver damage in male rats. METHODS: Forty males of a new model of albino rats (Wistar strain) (175–205 g) were divided into four groups. The 1st Group (G1) was the negative control group, the remaining rats were injected with CCl(4) (1 ml/kg body weight) with equal amount of olive oil on the 1st and 4th day of every week for 4 weeks. The 2nd group (G2) was the positive control, the 3rd group (G3) and the fourth group (G4) were treated orally with N. sativa oil and olive oils using stomach tube. RESULTS: The positive control group showed an increase in hepatic enzymes, total bilirubin, creatinine, uric acid, lipid peroxide total cholesterol, triglyceride, low density lipoprotein, very low density lipoproteins, interleukin-6, and a decrease in antioxidant enzymes, high density lipoprotein cholesterol, a decrease in total protein and albumin an when compared with negative control group. Histology of the CCl(4) treated group revealed inflammation and damage of liver cells. Treating the hepatotoxic rats with olive oil and N. sativa oil showed a significant improvement in all biochemical tests compared with the positive CCl(4) control group. In addition, the liver tissues of olive oil treated group showed mild improvement in inflammatory infiltration and in N. sativa oil treated group showed normal hepatocytes with no evidence of inflammation. CONCLUSION: This study revealed that olive oil and N. sativa oil have a protective effect against CCl(4)-induced hepatotoxicity in male rats. Nigella sativa oil was more effective than olive oil.